RIBA DAN BUNGA PADA BANK DALAM PERSPEKTIF ISLAM: Konsep, Implementasi serta Dampak Riba dan Bunga Kepada Perekonomian - Amirullah, Safira (Program Studi Ekonomi Syariah (ES) STAI Nahdlatul Ulama (STAINU) Malang, 2023)
Interest is an addition to the borrowing transaction of funds that can be calculated where it does not carry out a process of prior consideration of the usefulness of the loan. At present, many Muslim communities cannot avoid what they do with conventional banking, which in conventional banking itself, many know that the system it runs contains an element of interest. However, sharia banking emerged, in which Islamic banking did not use a system called interest, therefore sharia banking is expected to continue to be consistent with the mudharabah system. By reviewing the literature which he does by reviewing books in depth and writing or even a sentence about interest and usury. We can find out what the concept of interest and usury is like from the perspective of fiqh and economics and can also find out the interpretation of interest and usury on banking as well as the impact of interest and usury on the economy.